Investigation of properties of new thermoelectric material Lu1-xScxNiSb - Romaka, V.A.; Stadnyk, Yu.V.; Romaka, V.V.; Demchenko, P.Yu.; Romaka, L.P.; Pashkevych, V.Z.; Horyn, A.M.; Horpenyuk, A.Ya. (Journal of Thermoelectricity, 2021)
The crystalline and electronic structures, thermodynamic, kinetic, energy and magnetic properties of the thermoelectric material Lu1-xScxNiSb at temperatures T = 80 – 400 K have been studied. Depending on the concentration of the alloying component in the solid solution Lu1-xScxNiSb, different mechanisms of Sc atoms entering the semiconductor matrix have been established, which leads to different rates of generation of structural defects of acceptor and donor nature. The ratio of the concentrations of existing defects of donor and acceptor nature determines the position of the Fermi level εF and the conduction mechanisms in Lu1-xScxNiSb. The investigated solid solution Lu1-xScxNiSb is a promising thermoelectric material. Bibl. 18, Fig. 8.